Inflammation management in acute diverticulitis: current perspectives - Ceresoli M (Dove Medical Press, 2018)
Marco Ceresoli,1,2 Giulia Lo Bianco,1,2 Luca Gianotti,1,2 Luca Nespoli1,2 1Department of General Surgery, San Gerardo Hospital, University of Milano-Bicocca, Monza, Italy; 2School of Medicine and Surgery, University of Milano-Bicocca, Milan, Italy Abstract: The pathogenesis of diverticular disease and acute diverticulitis is still unclear and many different hypotheses have been formulated. Seemingly, there are several related factors such as chronic inflammation, gut microbiome, obesity and the immunogenic properties of fat tissue and diet. Inflammation plays a pivotal role in diverticular disease and acute diverticulitis. The aim of the present review is to investigate the role of inflammation in diverticular disease as well as in mild and complicated acute diverticulitis with a focus on current research and treatment perspectives. Keywords: acute diverticulitis, inflammation, diverticular disease.